2023
DOI: 10.1021/acs.nanolett.2c04346
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Atomic Force Microscopy Reveals Spontaneous Nucleosome Sliding of H2A.Z at the Subsecond Time Scale

Abstract: Nucleosome dynamics, such as nucleosome sliding and DNA unwrapping, are important for gene regulation in eukaryotic chromatin. H2A.Z, a variant of histone H2A that is highly evolutionarily conserved, participates in gene regulation by forming unstable multipositioned nucleosomes in vivo and in vitro. However, the subsecond dynamics of this unstable nucleosome have not been directly visualized under physiological conditions. Here, we used high-speed atomic force microscopy (HS-AFM) to directly visualize the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…It is also possible that H2A.Z can stabilize the histone octamer in a tail-dependent fashion as measured in our assay, while simultaneously weakening the histone-DNA interactions at the DNA entry and exit points as detected by cryo-EM. However, recent AFM studies suggest that the N-terminal part of the histone, not the C-terminal, controls nucleosome-DNA binding strength 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible that H2A.Z can stabilize the histone octamer in a tail-dependent fashion as measured in our assay, while simultaneously weakening the histone-DNA interactions at the DNA entry and exit points as detected by cryo-EM. However, recent AFM studies suggest that the N-terminal part of the histone, not the C-terminal, controls nucleosome-DNA binding strength 34 .…”
Section: Discussionmentioning
confidence: 99%
“…4F). The N-terminal part of H2A.Z has a marked effect on the sliding of the nucleosome on the DNA 34 , while the C-terminal tag is expected to directly interfere with interactions involving the tail. Tagged H2A.Z also appears to be localized in a scattered rather than dominantly peripheral manner in the nucleus, compared with ZAbA-detected native H2A.Z (Suppl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Previously, we visualized spontaneous nucleosome sliding events in nucleosomes containing H2A.Z.1, an H2A variant, with a temporal resolution of 0.3 s through optimization of the AFM substrate. 34 Building on this methodology, we employed HS-AFM to observe the dynamics of tail-less nucleosomes. Our results showed that the absence of histone tails causes a 10-fold increase in the frequency of nucleosome sliding and DNA unwrapping/wrapping events.…”
mentioning
confidence: 99%
“…Experimental studies indicate that the sliding rates depend on the DNA sequence and length of the DNA fragment between the neighboring nucleosomes. It has been also suggested that the inherent mobility of nucleosomes can be altered by the deletion of histone tails and/or mutations in histone proteins . Recent high-speed atomic force microscopy investigations , have successfully captured spontaneous reversible sliding of mononucleosomes on a subsecond time scale with high temporal resolution. Another single-molecule study probed the diffusion of nucleosomes with a base-pair scale resolution on natural, biologically relevant sequences.…”
mentioning
confidence: 99%